Enhancing Spermatozoa Quality and Spermatogenic Cell in Hyperglycemic Mice (Mus musculus L.) with Sambung Nyawa (Gynura procumbens) and Mahagany (Swietenia mahagoni jacq) extracts, Alone and in Combination - Sukarjati; Umi Nurhayati; DesyaTresty Medistriani (Jurnal Penelitian Pendidikan IPA, 2024)
This study aimed to investigate the effect of the ethanol extract of sambung nyawa (Gynura procumbens) leaves, mahogany (Swietenia mahagoni jacq) seeds, and their combination on the motility, viability, morphology, and concentration of spermatozoa, spermatogonia, spermatocytes, and spermatids in hyperglycemic mice induced with 10% dextrose. A total of 48 male mice were used as experimental animals, and the extracts were administered orally for 35 days. On day 36, spermatozoa and testicular tissues were collected for analysis. The results showed that the extracts at various doses had the potential to reduce blood glucose levels and improve the motility, viability, morphology, and concentration of spermatozoa and germ cells in hyperglycemic mice. Result:The combination of sambung nyawa leaves and mahogany seeds at a dose of 150:150 mg/kg BW was found to be the most effective in reducing blood sugar levels and improving sperm parameters. Therefore, these extracts have the potential to be used as alternative herbal ingredients with similar effects to metformin in reducing diabetes and improving fertility.